Analysis (Descriptive Analysis) Recruitment and Selection of Educational Personnel - Taslimah, Diana; Astuti, Puji; Gayatri, Ratna; Ahmad, Fahad (Departement of PAI, Universitas Majalengka, 2023)
This Article discusses the recruitment and selection process for education personnel as a crucial step in building a quality education system. Effective recruitment and selection not only ensure that education personnel have the right qualifications, but also strengthens the foundation of educational institutions. This journal explores innovative recruitment strategies, including the use of modern technology and social networks to reach potential educational candidates. In addition, the importance of detailing selection criteria that match the demands of the job and the values of the educational institution is emphasized. In the context of selection, this journal discusses holistic evaluation methods, including interviews, competency tests, and behavioral assessments, to ensure that educational staff not only have adequate technical knowledge, but are also committed to the educational mission. In addition, this journal highlights the importance of paying attention to diversity in recruitment and selection, to create an inclusive and representative learning environment. Emphasis is placed on fairness in the selection process to prevent discrimination and ensure equal opportunities for all candidates. By discussing all these aspects, this article aims to provide comprehensive insight into how recruitment and selection of educational personnel can be an important pillar in achieving the goal of quality education. Through a careful and progressive approach in selecting educational personnel, educational institutions can ensure that they have a team that is competent and committed to forming a superior future generation.